Pengaruh atribut produk dan layanan lembaga pembiayaan terhadap keputusan pembelian sepeda motor Honda Vario di Kota Jambi - Bestina Sri Juniar; Johannes Johannes; Sigit Indrawijaya (Jurnal Dinamika Manajemen, 2019)
This study aims to explain the influence of financial institution product and service attributes on purchasing decisions of Honda Vario Jambi motorbikes in Jambi City. The sample is 140 users of Honda Vario motorcycles, with the sampling technique used is Purposive sampling. Validity and reliability test results show that the research instrument is valid and reliable. The data analysis used in this study is multiple linear regression analysis using SPSS Version 22 software. The results show that purchasing decisions are influenced by the financial product and service attributes significantly and partially the decision to purchase Honda vario motorcycles in Jambi City is influenced by attributes financial institution products and services. In the discussion, the results of the study showed that the presence of product attributes and services of financial institutions could increase sales of Honda Vario motorcycles. To achieve this level of sales, the company must continue to present superior product attributes and maintain good cooperative relations with financing institutions that provide financial institution services.